Color Variation in a Novel Glycine soja Mutant W4‐S1 with Pinkish‐White Flowers Is Controlled by a Single Recessive Allele at the W4 Locus. Issue 6 (23rd August 2017) - Park, Gyu Tae; Sundaramoorthy, Jagadeesh; Lee, Seokhyung; Lee, Jeong‐Dong; Kim, Jeong Hoe; Park, Soon‐Ki; Seo, Hak Soo; Chung, Gyuhwa; Song, Jong Tae
Abstract : Dihydroflavonol‐4‐reductase (DFR) plays a crucial role in anthocyanin biosynthesis. In cultivated soybean [ Glycine max (L.) Merr.], the W3 and W4 loci encode DFR1 and DFR2, respectively, and are epistatic to each other. In this study, we discovered a new flower color variant of Glycine soja (L.) Merr., CW13133, which has pinkish‐white flowers, and investigated the genetic and molecular basis of the variation in flower color. We found that the W4 locus encoding DFR2 was responsible for the variation in flower color. Sequence analysis of the DFR2 gene of CW13133 revealed three single‐nucleotide polymorphisms (SNPs). Among these, an SNP (T to C) at nucleotide position 2856 was noteworthy, since it led to a change in an amino acid residue (leucine to proline) at position 326 of DFR2. This amino acid substitution was located in a region that is highly conserved among different plant species. The new allele was designated w4‐s1 . A cleaved amplified polymorphic sequence analysis showed cosegregation of the w4 ‐ s1 allele with pinkish‐white flowers. Interestingly, DFR1 was not expressed in the w4 ‐ s1 mutant, indicating that the W3 locus has no association with flower color variation. Based on a randomized comparative analysis using 10 different purple‐flowered accessions of G . soja, we provide evidence for the nonassociation of DFR1 expression with total anthocyanin contents and flower color determination in G . soja . In conclusion, we found that the W3 locus in G . soja does not contribute to flower color determination, and consequently there is no epistatic interaction between the W3 and W4 loci, as shown in G . max .